2022
DOI: 10.1126/science.add4153
|View full text |Cite
|
Sign up to set email alerts
|

Multiple lineages of monkeypox virus detected in the United States, 2021–2022

Abstract: Monkeypox is a viral zoonotic disease endemic in Central and West Africa. In May 2022, dozens of non-endemic countries reported hundreds of monkeypox cases, most with no epidemiological link to Africa. We identified two lineages of monkeypox virus (MPXV) among two 2021 and seven 2022 U.S. monkeypox cases: the major 2022 outbreak variant, B.1, and a minor contemporaneously sampled variant called A.2. Analyses of mutations among these two variants revealed an extreme preference for GA-to-AA mutations indicative … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
215
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(233 citation statements)
references
References 37 publications
18
215
0
Order By: Relevance
“…However, it has been suggested that host APOBEC3 in viral evolution with signs of potential human adaptation of MPXV in ongoing microevolution (Isidro et al, 2022). Gigante et al reported that APOBEC3 activity has been recurrent and dominant in West African MPXV evolution (2017-2022) recently (Gigante et al, 2022). When compared with previous MPXV sequences, many mutations in the 2022 MPXV sequences were 5’ GA-to-AA, suggesting APOBEC3 activity (O’Toole and Rambaut, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been suggested that host APOBEC3 in viral evolution with signs of potential human adaptation of MPXV in ongoing microevolution (Isidro et al, 2022). Gigante et al reported that APOBEC3 activity has been recurrent and dominant in West African MPXV evolution (2017-2022) recently (Gigante et al, 2022). When compared with previous MPXV sequences, many mutations in the 2022 MPXV sequences were 5’ GA-to-AA, suggesting APOBEC3 activity (O’Toole and Rambaut, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The current Monkeypox outbreak in USA represents the circulation of MPXV lineage A.2 from 2021 which has evolved from lineage A that caused the Nigeria outbreak in 2017-2018. 14 The MPXV genome retrieved from con rmed Monkeypox cases with travel history from UAE to India also demonstrated the circulation of A.2 lineage in UAE. Unfortunately, no epidemiological data is available for the introduction of MPXV to UAE.…”
Section: Laboratory Analysismentioning
confidence: 96%
“…The remaining non-host reads were assembled using SPADES v3.15.3 (Antipov et al, 2016;Prjibelski et al, 2020) in rnaviral mode. A fully ordered MPXV genome sequence was generated using ABACAS v1.3.1 (Assefa et al, 2009), based on the MPXV isolate MPXV_USA_2022_MA001 (Nextstrain subclade IIb lineage B.1) sequence (GenBank #ON563414.3) (Gigante et al, 2022). The independently obtained de novo assemblies and reference-based consensus genomes obtained from swab 353R were aligned using MAFFT v7.475 (Katoh et al, 2019) and visually inspected for variation using Jalview v2.11.0 (Waterhouse et al, 2009).…”
Section: De Novo Assembly and Annotation Of Subclade II Lineage B1 Mp...mentioning
confidence: 99%
“…Among Clade IIb, B1 strains show 16 We propose this genome for sample 353R as a high-quality complete reference genome, HQG 41 . We compared our 198,547 bp HQG to MPXV-M5312_HM12_Rivers (NC_063383.1) and MPXV_USA_2022_MA001 (ON563414.3) 13 (Table 3). Both 353R and ON562414.3 genomes show the same 67 SNPs called against the NC_063383.1 reference genome.…”
Section: A Complete High-quality Monkeypox Genome Assembly and Annota...mentioning
confidence: 99%
See 1 more Smart Citation